Russian Language as the Instrument of "Soft Power" In the Countries of Central Asia - O.B. Molodov (Дискурс Пи, 2017)
The article discusses the possibility of using the Russian language as the factor of "soft power" in Central Asia. Despite the change in the ethnic composition of the population of Central Asia, the Russian language has retained a high potential of expanding the political influence of Russia in the region. This article was prepared on the basis of statistical information and previously conducted studies on this issue.